Low HDL Cholesterol is Associated with Reduced Bleeding Risk in Patients who Underwent PCI: Findings from the PRACTICE Study - Zheng, Ying-Ying; Wu, Ting-Ting; Hou, Xian-Geng; Yang, Yi; Yang, Hai-Tao; Pan, Ying; Xiu, Wen-Juan; Ma, Xiang; Ma, Yi-Tong; Yang, Xin-Ling; Xie, Xiang (Thrombosis and Haemostasis, 2023)
Background We sought to examine the dose–response relationship between high-density lipoprotein cholesterol (HDL-C) and bleeds in coronary artery disease (CAD) patients who underwent percutaneous coronary intervention (PCI).Methods All the 15,250 participants were from the Personalized Antiplatelet Therapy According to CYP2C19 Genotype in Coronary Artery Disease (PRACTICE) study, which is a large, single-center, prospective cohort study based on case records and a follow-up registry performed in the First Affiliated Hospital of Xinjiang Medical University from December 2016 to October 2021. We divided all the patients into five groups according to their HDL-C levels: the ≤35 mg/dL group (n = 4,732), 35 to 45 mg/dL group (n = 6,049), 45 to 55 mg/dL group (n = 2,826), 55 and 65 mg/dL group (n = 1,117), and >65 mg/dL group (n = 526). The incidence of bleeds, mortality, ischemic events, and net adverse clinical events (NACEs) among the five groups was compared.Results A total of 713 bleeds, 1,180 ischemic events, 456 deaths, and 1,893 NACEs were recorded during the up to 60-month follow-up period. After adjusting for confounders, we observed a nonlinear relation for bleeds, with the highest risk at intermediate HDL-C levels (45–55 mg/dL). We also identified a dose–response relationship for ischemic events. A threshold value of HDL-C ≤35 mg/dL (adjusted hazard ratio = 0.560, 95% confidence interval: 0.360–0.872, p = 0.010) was associated with a decreased risk for bleeds in the multivariable Cox regression model. The results were consistent in multiple sensitivity analyses and propensity score-matching analysis.Conclusion In the present study, a nonlinear association was identified between HDL-C levels and bleeds in CAD patients who underwent PCI, with a higher risk at intermediate levels. However, further multicenter studies are warranted.
Keywords: high-density lipoprotein cholesterol; bleeds; antiplatelet; coronary artery disease